Studi Farmakognostik Tanaman Harendong Bulu (Clidemia Hirta) asal Maluku - Aulia Debby Pelu; Jayanti Djarami (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Harendong Bulu with the Latin name Clidemia hirta is a plant that belongs to the Melastomataceae family, this plant usually has medicinal properties. This study aims to obtain morphological, anatomical, organoleptic data, and identify the chemical content of the harendong bulu (Clidemia hirta) plant. The research design used is an experimental laboratory. Morphological examination showed that the harendong bulu (Clidemia hirta) belongs to the class of magnoliopsida with woody stems, the shape of the stem is round, the surface of the stem is hairy, scaly and brown in color and the root system is tapped. Anatomical examination showed that the harendong bulu (Clidemia hirta) plant has epidermis, endodermis, cuticle, stomata, vessels, xylem and phloem, periskel, cortex, and calcium oxatate crystals. On organoleptic examination, the leaves of Harendong Bulu (Clidermia hirta) have a bitter and sweet taste and a characteristic odor, while the stems have a bitter taste and a characteristic odor, and the roots have an astringent bitter taste and odorless. Chemical identification of harendong bulu leaf powder obtained positive results for tannins (catechols and pyrogalotanins), dioxyanthraquinones, steroids, saponins, glycosides and phenols.Harendong Bulu with the Latin name Clidemia hirta is a plant that belongs to the Melastomataceae family, this plant usually has medicinal properties. This study aims to obtain morphological, anatomical, organoleptic data, and identify the chemical content of the harendong bulu (Clidemia hirta) plant. The research design used is an experimental laboratory. Morphological examination showed that the harendong bulu (Clidemia hirta) belongs to the class of magnoliopsida with woody stems, the shape of the stem is round, the surface of the stem is hairy, scaly and brown in color and the root system is tapped. Anatomical examination showed that the harendong bulu (Clidemia hirta) plant has epidermis, endodermis, cuticle, stomata, vessels, xylem and phloem, periskel, cortex, and calcium oxatate crystals. On organoleptic examination, the leaves of Harendong Bulu (Clidermia hirta) have a bitter and sweet taste and a characteristic odor, while the stems have a bitter taste and a characteristic odor, and the roots have an astringent bitter taste and odorless. Chemical identification of harendong bulu leaf powder obtained positive results for tannins (catechols and pyrogalotanins), dioxyanthraquinones, steroids, saponins, glycosides and phenols.